Congenital anomalies in newborns to women employed in jobs with frequent exposure to organic solvents - a register-based prospective study - Talykova Ljudmila V; Vaktskjold Arild; Nieboer Evert (BMC, 2011)
Abstract Background The foetal effects of occupational exposure to organic solvents in pregnancy are still unclear. Our aim was to study the risk of non-chromosomal congenital anomalies at birth in a well-defined population of singletons born to women employed as painters and spoolers in early pregnancy, compared to women in non-hazardous occupations. Method The study population for this prospective cohort study was singleton newborns delivered to working mothers in the industrial community of Mončegorsk in the period 1973-2005. Occupational information and characteristics of the women and their newborns was obtained from the local population-based birth register. Results The 597 women employed as painters, painter-plasterers or spoolers had 712 singleton births, whereof 31 (4.4%) were perinatally diagnosed with 37 malformations. Among the 10 561 newborns in the group classified as non-exposed, 397 (3.9%) had one or more malformations. The overall prevalence in the exposed group was 520/10 000 births [95% confidence limits (CL): 476, 564], and 436/10 000 births (95% CL: 396, 476) in the unexposed. Adjusted for young maternal age, smoking during pregnancy, maternal congenital malformation and year of birth, the odds ratio (OR) was 1.24 (95% CL: 0.85, 1.82); for multiple anomalies it was 1.54 (95% CL: 0.66, 3.59). The largest organ-system specific difference in prevalence between the two groups was observed for malformations of the circulatory system: 112/10 000 (95% CL: 35, 190) in the exposed group, and 42/10 000 (95% CL: 29, 54) in the unexposed, with an adjusted OR of 2.03 (95% CL: 0.85, 4.84). The adjusted ORs for malformations of the genital organs and musculoskeletal system were 2.24 (95% CI: 0.95, 5.31) and 1.12 (95% CI: (0.62, 2.02), respectively. Conclusion There appeared to be a higher risk of malformations of the circulatory system and genital organs at birth among newborns to women in occupations with organic solvent exposure during early pregnancy (predominantly employed as painters). However, the findings were not statistically conclusive. Considering that these two categories of malformations are not readily diagnosed perinatally, the difference in prevalence between the exposed and unexposed may have been underestimated.